Application of a foam-based functionally graded porous material flow-distributor to PEM fuel cells. (1st September 2022) - Kermani, M.J.; Moein-Jahromi, M.; Hasheminasab, M.R.; Ebrahimi, F.; Wei, L.; Guo, J.; Jiang, F.M.
Abstract: Application of a recently developed functionally graded porous material (FGPM) model to foam-based flow-distributor (FFD) in PEM fuel cells (FCs) is performed here. The volumetric power density (VPD) of the cell is compared with that of a conventional ribbed/channel parallel-serpentine one with 4-parallel channels (in short, 4-PS). Significant enhancement in VPD% is observed w.r.t. 4-PS case. Say, at current density 1 A cm −2, the cell with FGPM-FFD provides 84% enhancement vs. 4-PS. The contributions to the enhancement come from two sources: (i) reductions in the cell volume and (ii) increases in generated electrical power. For the flow distributors studied here, the active area is fixed at 50 × 50 mm 2 . While the 4-PS cell thickness is determined to be: 3.75 mm, from which 2 × 0.275 mm belongs to the gas diffusion layers (GDLs). In the absence of GDLs in the foam-based cells, the cell thicknesses reduce to 3.2 mm (∼15% reduction in cell volume). Moreover, the generated electrical power is also higher in FGPM cells due to the rib-less nature of the foam-based flow distributors. For example, at 1 A cm −2, the FGPM cell produces 57% more power than the 4-PS base case. At higher current densities, the enhancement is even higher. Highlights: Innovative Functionally Graded Porous Material (FGPM) foam used as flow distributor (FD). As PEM fuel cells FD, U-type FGPM foam vs. parallel-serpentine (PS) are considered. Performances of FDs with 4 or 6 PS channels are compared with FGPM foam FD. Cells have same active area; FGPM cell with 14% less volume, and higher power. For the cases studied, volumetric power density (VPD) of the FGPM cell is higher by 84%.